The combination of insulin-like growth factor 2, Alpha-Actinin-3, and Angiotensin-converting enzyme gene polymorphisms in judo athletes: A pilot study - Itaka, T.; Agemizu, K.; Aruga, S.; Machida, S. (Juntendo Medical Journal, 2016)
Objective: The purpose of this study was to investigate the association between the combination of insulin-like growth factor 2 (IGF2), alpha-actinin-3 (ACTN3), and angiotensin-converting enzyme (ACE) gene polymorphisms and judo status.